EXPRESSIONS OF ESTROGEN OCCUPIED RECEPTOR(EoR) AND PROGESTERONE OCCUPIED RECEPTOR(PoR) AND C- erbB- 2 ONCOPROTEIN IN HUMAN NASOPHARYNGEAL CARCINOMAS - Xie, Zuofu; Lin, Xiandong; Zhang, Jingshi (Chinese Journal of Cancer Research, 2013)
It is first reported here that estrogen occupied receptor (EoR) and progesterone occupied receptor (PoR) expressed in cancenms tissues (59.57% and 82.98% respectively) and morphologically normal epithelimn (50---77.78% and 70--88.89% respectively) in nasopharyngeni carcinomas (NPCs) with insignificant difference (P >0.05). Positive rates of EoR and PoR increased greatly in clinical stage III and IV, compared with in II ( P0.05). Positive rate of C- erbB- 2 was 19.15% in cancerous celis,and 9.68% in stage III and 66.67% in IV in NPCs(P 0.05). These findings suggest that EoR or PoR may be correlated with aggravation but not genesis and node metastasis in NPCs and that C- erbB- 2 may be correlated with aggravation and promotion of formation of node metastasis in NPCs.